The Role of the Four-Wheel Patrol Unit of the Sabhara Unit in Preventing Motor Vehicle Theft - Hurlatu, Stevy Yohanes (Advances in Police Science Research Journal, 2024)
This research is motivated by the high number of cases of fraud in Cirebon City Police. Prevention is needed by the Police in the form of police patrols. However, the implementation of the Cirebon City Police patrol was not optimal. The purpose of this research is to describe and analyze the implementation of the role of patrol and the factors that influence it. Conceptual literature uses management theory. The concept used is the concept of patrol and the concept of motorized theft which is used as an analysis knife in the discussion. The study was conducted with a qualitative approach. Data sources include primary data and secondary data. Data collection techniques used are through interviews, observation and document review. The analysis used data reduction, data presentation and conclusion drawing. The results of the study found that the implementation of the role of patrols was not optimal, there were internal and external factors in the implementation of patrols, the lack of members, personnel had not conducted training, the implementation of police patrols carried out by officers was not in accordance with the regulations on patrols and SOP patrols, targets of police patrols that adjust to the conditions of the Cirebon City area whose jurisdiction joins several Cirebon district sub-districts and the limited number of members makes it difficult for officers. Efforts made to optimize patrols are Copyright condition patrols, enhanced police activities (KKYD), patrols in the target area and time of frequent cases of fraud. Suggestions from researchers are (1) providing rewaerd and punishment to patrol members so that the implementation of the patrol achieves the expected results and objectives (2) Sumda Bag provides training and vocational education to patrol members to improve their abilities. (3) Cambang Sambang Saturday Program is reviewed and evaluated so that in the future it will be one of the right efforts for Cirebon City Police in preventing the theft of motorized vehicles.